A model proposal explaining the influence of smartphone addiction related factors on high school students’ academic success - KARACA, FERİDE (My University, 2024)
An exploratory sequential mixed-method study is designed to develop and test a comprehensive model explaining the relationships between factors associated with smartphone addiction and high school students’ academic achievement. Involving two main phases of qualitative and quantitative, focus group discussions with high school students and interviews with teachers were conducted in the first phase, both to decide on the factors and to reveal the relationships between the factors in the model. According to the qualitative results, the most important factors were found as social media usage, cyberloafing, academic procrastination, external and internal academic locus of control. Then, a hypothesis model involving these factors was developed to explain high school students\" academic achievement. Obtained from 410 high school students, quantitative data are collected online by the use of some scales measuring the factors included in the model. Using the path analysis method, the hypothesis model was tested, and it was observed that the model fit the data well. As a result, the factors that most influence academic achievement were found as duration of social media usage, external academic locus of control, smartphone addiction, internal academic locus of control, academic procrastination, and cyberloafing respectively. The uniqueness of the presented model in this research is believed to lie in its holistic perspective on the relationships between smartphone addiction and related factors, and their effects on academic achievement. Looking from a big picture, this model is expected to provide a roadmap for practitioners and decision-makers in terms of how to improve students’ academic achievement.
Keywords: Sosyal ve Beşeri Bilimler; Sosyoloji; Kütüphanecilik; Eğitim; Social Sciences and Humanities; Sociology; Library Sciences; Education; Sosyal Bilimler (Soc); Sosyal Bilimler Genel; Eğitim Ve Eğitim Araştırması; Bilgi Bilimi Ve Kütüphane Bilimi; Social Sciences (Soc); Social Sciences General; Education & Educational Research; Information Science & Library Science; Sosyal Bilimler ve Beşeri Bilimler; Kütüphane ve Bilgi Bilimleri; Social Sciences & Humanities; Library and Information Sciences; Academic achievement; Academic locus of control; Academic procrastination; Duration of social media use; Path analysis; Smartphone addiction